Hubungan Tingkat Pengetahuan Pasien Hipertansi Terhadap Kepatuhan Minum Obat Pada Pasien Rawat Jalan Di Rumah Sakit Royal Prima - Adelia Pratiwi; Muhammad Yunus; Roy Indrianto Bangar (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Hypertension s a chronic condition with a high prevalence that can lead to cardiovascular complications if patients do not adhere to medication regimens and the medication adherence is on of the primary key to therapeutic success. However, low adherence rates remain a significant challenge, often linked to insufficient patient understanding. This study aimed to analyze the relationship between the level of knowledge of hypertensive patients and their medication adherence at Royal Prima Hospital. This research method employed a quantitative correlational design with a cross-sectional approach involving 78 outpatient respondents selected through purposive sampling. Demographic data were analyzed using the Chi-Square Test, while the relationship between the main variables was tested with Spearman Correlation. The results showed that the majority of respondents had a sufficient level of knowledge (52.6%) and moderate adherence (48.7%). The Spearman Correlation test yielded a coefficient value (rₛ) of 0.803 with p < 0.001, indicating a very strong and significant positive relationship between the level of knowledge and medication adherence. Conversely, the Chi-Square Test results showed no significant association between demographic characteristics and adherence. It is concluded that knowledge is a crucial determinant influencing treatment adherence among hypertensive patients.